HUBUNGAN KEMAMPUAN BERPIKIR LOGIS DENGAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH GENETIKA - Murni, Dewi (Jurnal Pendidikan Biologi, 2016)
This research aimed to described the student logical thinking skills and learning outcomes, analyze the relationship of both, and explain the contribution of logical thinking skills to the students learning outcomes in genetics. The subjects were 71 students from the Department of Biology Education, second semester of academic year 2014 / 2015. The research was conducted using descriptive and correlational design. Measurement of the student logical thinking, have done using Test of Logical Thinking (TOLT), while learning outcomes measured by cognitive test questions. The correlation between the both variables was analyzed by product moment correlation. The results showed that 54% of the students have the beginning of the formal category of logical thinking skill with an average value of 4.03. The data also showed that 45% of the students have to the low category of learning outcomes with an average value of 54.86. The correlation, r = 0.609 and a significance value of 6.372 indicates that there is a high correlation between the logical thinking skill with the students learning outcomes in genetics. The analysis also showed that the student logical thinking accounted for 42.35% of the student learning outcomes.